«Плпулн Аварайри» («Соловей Аварайра») Гевонда Алишана в музыке - Асатрян, Aнна (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Հայ բանասեր, պատմաբան, աշխարհագրագետ, թարգմանիչ, Վենետիկի Մխիթարյան Միաբանության անդամ Հայր Ղևոնդ Ալիշանը (1820-1901) գրական ասպարեզ իջավ որպես ինքնատիպ բանաստեղծ: Եվ պատահական չէ, որ նրա պոեզիան արժանացավ հայ (և ոչ միայն հայ) կոմպոզիտորների ուշադրությանը: Ալիշանի «Պլպուլն Աւարայրի» պոեմը կարևոր դեր կատարեց հայ երաժշտության պատմության մեջ՝ իր վըա հրավիրելով հայ կոմպոզիտորների ուշադրությունը թե' բանաստեղծի օրոք, թե' նրա մահից հետո: 1899-ին Եկմալյանը ստեղծեց «Պլպուլն Աւարայրի» a cappella խմբերգը խառը երգչախմբի համար, իսկ տարիներ անց՝ սփյուռքահայ կոմպոզիտոր Գուրգեն Ալեմշահը՝ «Պլպուլն Աւարայրի» a cappella խմբերգը խառը երգչախմբի համար: Մ.Եկմալյանի «Պլպուլն Աւարայրի» խմբերգը, շնորհիվ Հովհաննես Չեքիջյանի, 1963-ին առաջին անգամ հնչեց Երևանում, հաստատուն տեղ գրավելով Հայաստանի ազգային ակադեմիական երգչախմբի երկացանկում: Այն մինչ օրս էլ ապրում է լիարժեք համերգային կյանքով' հնչելով Հայաստանում և արտասահմանում: Եկմալյանական «Պլպուլը» հիմք դարձավ նոր ստեղծագործությունների համար. Գրիգոր Սյունին ստեղծեց «Ոհ՜, դու բարեկամ (Պլպուլն Ավարայրի)» վերնագրով a cappella խմբերգը, իսկ Ալեքսանդր Հարությունյանի շնորհիվ այն մուտք գործեց գործիքային երաժշտություն: Կոմպոզիտորը եկմալյանական մեղեդին վարպետորեն օգտագործեց իր «Մեր հին երգերը» ռապսոդիայում։ The Armenian linguist, historian and translator, member of the Mkhitarist Congregation, Ghevond Alishan (1820-1901) stepped into the literary world as a unique poet. Quite predictably, his poetry drew the attention of the Armenian, as well as other composers. The poem “The Nightingale of Avarayr” (1847) by Alishan has played an important role in the history of the Armenian music. Armenian composers addressed the poem both during Alishan’s lifetime and after his death, having created choral capella pieces for mixed choir. The classic of Armenian music Makar Yekmalyan (1856-1905) wrote a choral work “The Nightingale of Avarayr” in 1899, and years later, Gurgen Alemshah (1907-1947) addressed the same poem. The choral piece by M. Yekmalyan “The Nightingale of Avarayr” , that had fallen into oblivion after the composer’s death, was brought back to life in 1963 thanks to the efforts of the young conductor Ohannes Tchekidjian. After its Yerevan debut, “The Nightingale of Avarayr” has occupied its solid place in the repertoire of the National Academic Choir of Armenia, and to date, it lives a fullfledged concert life, having become one of the signatures of Maestro Tchekidjian and the Armenian Capella. Yekmalyan’s “ Nightingale” paved the way for new musical pieces. Thus, Grigor Syuni wrote a cappella choral work, while owing to Alexander Harutyunyan, the “Nightingale” became part of instrumental music: the composer used the tune of Yekmalyan’s “ Nightingale” in the prelude to his rhapsody “Our Old Songs” (1974).
Keywords: Искусство